2015
DOI: 10.1002/chem.201405507
|View full text |Cite
|
Sign up to set email alerts
|

Solvent Influence on Cellulose 1,4‐β‐Glycosidic Bond Cleavage: A Molecular Dynamics and Metadynamics Study

Abstract: We explore the influence of two solvents, namely water and the ionic liquid 1-ethyl-3-methylimidazolium acetate (EmimAc), on the conformations of two cellulose models (cellobiose and a chain of 40 glucose units) and the solvent impact on glycosidic bond cleavage by acid hydrolysis by using molecular dynamics and metadynamics simulations. We investigate the rotation around the glycosidic bond and ring puckering, as well as the anomeric effect and hydrogen bonds, in order to gauge the effect on the hydrolysis me… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
15
0

Year Published

2015
2015
2019
2019

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 30 publications
(18 citation statements)
references
References 109 publications
3
15
0
Order By: Relevance
“…Concerning reactivities (Table ), the QM/MM calculations with the large QM region indicate that cellobiose is by 8 kcal mol −1 easier to hydrolyse than the cellulose chain, while there are no striking differences between the different regions of the chain. This is consistent with our previous metadynamics simulations for the same cellulose models, which gave no conformational differences between the regions of the chain and cellobiose in water …”
Section: Resultssupporting
confidence: 93%
“…Concerning reactivities (Table ), the QM/MM calculations with the large QM region indicate that cellobiose is by 8 kcal mol −1 easier to hydrolyse than the cellulose chain, while there are no striking differences between the different regions of the chain. This is consistent with our previous metadynamics simulations for the same cellulose models, which gave no conformational differences between the regions of the chain and cellobiose in water …”
Section: Resultssupporting
confidence: 93%
“…[8] The specific influence of local mechanical forces on improving both reactivity and selectivity has been proven for aplethora of processes. [8b, 9] In view of the complex multistep nature of cellulose hydrolysis without mechanical force (only thermal activation), [10] we must decipher the catalytic influence of force on the protonation of the glycosidic oxygen atom (reaction step Rp), conformational changes of the pyranose six-ring (Rc), and cleavage of the glycosidic bond (Rb). To mimic cellulose,w ec onsidered am ethoxy derivative of cellobiose together with one hydronium ion as the proton source (Figure 1, top).…”
Section: Saeed Amirjalayer* Harald Fuchsa Nd Dominik Marxmentioning
confidence: 99%
“…At am olecular level, the b-1-4 glycosidic bond in cellulose is lockedb ya ne lectronic exo-anomerice ffect, which strongly stabilizes the glycosidicb ond ( Figure 2). [29] Conversely to ionic liquids, in water,h ydrogen bonds are, which contribute to maximizet he exo-anomeric effect and thus the recalcitranceo ft he glycosidicb ondt oh ydrolysis. [29] Conversely to ionic liquids, in water,h ydrogen bonds are, which contribute to maximizet he exo-anomeric effect and thus the recalcitranceo ft he glycosidicb ondt oh ydrolysis.…”
Section: Mechanismmentioning
confidence: 99%
“…[28] Indeed, this exoanomeric effect shortens the glycosidic bond length and prevents the ring from flipping from ac hair to an on-chair conformation, amandatory step before the cleavage of the glycosidic bond. [29] Conversely to ionic liquids, in water,h ydrogen bonds are, which contribute to maximizet he exo-anomeric effect and thus the recalcitranceo ft he glycosidicb ondt oh ydrolysis. Furthermore, DFT calculations have revealed that the anomeric oxygen is thel east basic site and thus is less likely to be protonated than other oxygen atoms ( Figure 2).…”
Section: Mechanismmentioning
confidence: 99%